7(f-3)+1=f+16

Simple and best practice solution for 7(f-3)+1=f+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(f-3)+1=f+16 equation:



7(f-3)+1=f+16
We move all terms to the left:
7(f-3)+1-(f+16)=0
We multiply parentheses
7f-(f+16)-21+1=0
We get rid of parentheses
7f-f-16-21+1=0
We add all the numbers together, and all the variables
6f-36=0
We move all terms containing f to the left, all other terms to the right
6f=36
f=36/6
f=6

See similar equations:

| 6x-11=61–3x= | | X2ª-5x+4=0 | | 2x-33=9x+7 | | x-45=5(x-2) | | 6x=25. | | x*x+x=52 | | -3=(p+3) | | 7x14=2x+11 | | 5x+x^2=52 | | 2x/3=357 | | 2(x+3)=3(5-x) | | x/5=42 | | 5x=4x10 | | 3+7x=-33+ | | 15x-20=-50 | | 7+m=4 | | 2x/1-x=0 | | 8x-2x-21=0 | | 4(x+3)=9x–10 | | 3+7x=44x+30 | | (x+7)+(x+3)=40 | | 9x-37=-1 | | 5x+10(x-3)=25 | | -221.5x-890x²=13.25 | | 2(4u-8)-3=3(u+7) | | 330p+130=2400 | | 2(3c-4)-5=c+7 | | 5(e-4)+3=2(e+9)-2 | | 3e-6=18 | | 2(3-h)+1=2(h-1)-11 | | 10x-30x^-2=0 | | -5x+3=60-2x |

Equations solver categories